Lithium-rich manganese-based positive electrode material and preparation method thereof, positive plate, lithium ion battery and power-related equipment

By doping anionic fluorine, Mg and high-valent cations in the lithium-rich manganese-based positive electrode material and using MSe@Te heterojunction coating, the problems of low initial Coulomb efficiency and rapid energy density decay are solved, and the further development is achieved High rate performance and cycle stability.

CN119481032AActive Publication Date: 2025-02-18XINXIANG TIANLI ENERGY CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510025616.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The initial Coulomb efficiency of existing lithium-rich manganese-based cathode materials is relatively low, and the energy density rapidly decays with circulation.

Method used

Doping anionic fluorine, the first cation Mg and the second cation with a lithium-rich manganese-based core, and coated with a MSe@Te heterojunction coating layer to regulate the charge distribution in the crystal structure, enhance the metamorphism of lithium ion, and improve the material rate performance and structural stability.

Benefits of technology

Through doping modification and heterojunction coating, the rate performance and cyclic stability of the lithium-rich manganese-based positive electrode material are improved, the loss of irreversible oxygen and the increase of interface impedance are reduced, and the electrochemical performance of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481032A_ABST
    Figure CN119481032A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive plate, a lithium ion battery and electric equipment, and relates to the technical field of new energy. The inner core is doped with fluorine ions, Mg ions and second cations with higher valence, and the coating layer is an MSe-Te heterojunction. Second cations are adopted to perform doping modification on the lithium-rich manganese-based material, and the rate capability of the material is improved by regulating and controlling charge distribution; after Mg element doping, a strong M-O bonding effect is formed in the material, so that the structural stability of a material crystal under a high-voltage condition is improved, and the loss of first-circle capacity is reduced. A part of oxygen in a bulk phase is replaced by fluorine doping, so that the bulk phase structure of a material crystal is stabilized, and irreversible phase change caused by oxygen release of the material in a high-voltage charging and discharging process is inhibited. The MSe-Te coating layer prevents the electrolyte from being in direct contact with the surface of the material, limits the increase of impedance in the circulation process, and solves the problem of poor rate capability of the lithium-rich manganese-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and electrical equipment. Background Art

[0002] As a positive electrode material for lithium-ion batteries, layered lithium-rich manganese-based oxides have excellent high-voltage electrochemical performance and sustainability, which can well meet the market's requirements for higher energy density and long driving range. In addition, the Mn element used to synthesize the positive electrode material is environmentally friendly, has high reserves in the earth's crust, and is inexpensive, giving lithium-rich manganese-based oxides eco-friendly and low-cost characteristics. Therefore, lithium-rich manganese-based oxides are regarded as very promising positive electrode materials for lithium-ion batteries.

[0003] However, the ionic conductivity of lithium-rich manganese-based materials is low, and under high voltage working conditions (greater than 4.5V), the Li in lithium-rich manganese-based positive electrode materials 2 MnO 3 The partially unstable oxygen atoms in the phase are removed from Li 2 MnO 3 In the lattice, O 2 The irreversible release of oxygen causes the structure of the lithium-rich manganese-based positive electrode material to change, so the initial coulombic efficiency of this type of material is low; in addition, under higher charging voltage conditions, the harmful substances produced by the decomposition of the electrolyte and the side reactions on the surface of the positive electrode material will consume a large amount of lithium ions, and the accumulation of by-products on the surface of the material will increase the interface impedance and interface instability, which in turn causes the energy density to decay rapidly with the cycle. Summary of the invention

[0004] The purpose of the present application is to provide a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and electrical equipment, aiming to solve the problem that the initial coulombic efficiency of the existing lithium-rich manganese-based positive electrode materials is low and the energy density decays rapidly with cycles.

[0005] To achieve the above objectives, the present application provides a lithium-rich manganese-based positive electrode material, comprising a lithium-rich manganese-based core and a coating layer coating the core, the core is doped with anion fluorine, a first cation Mg and a second cation, the valence state of the second cation is ≥+2, and the coating layer is a MSe@Te heterojunction coating layer, wherein M is selected from any one of Mo, W, Sn, and Bi.

[0006] In some embodiments, the second cation is selected from at least one of Y, Ta, La, Ce, Sr, and Sb.

[0007] In some embodiments, at least one of the following conditions is met: A. The lithium-rich manganese-based positive electrode material is a spherical particle; B. Calculated by the mass equivalent of element M, the addition amount of the heterojunction coating layer is 1500 ppm to 4000 ppm; C. The chemical general formula of the lithium-rich manganese-based core is: t Li 2 MnO 3 ·(1 - t) LiNO 2 , where 0 < t < 1, and N is selected from at least one of Ni, Co, and Mn; D. The lithium-rich manganese-based core includes a plurality of primary particles, and the aspect ratio of the primary particles is (1:1) to (5:1); E. The D50 of the lithium-rich manganese-based cathode material is 9.5 μm.

[0008] This application also provides a preparation method of the above lithium-rich manganese-based cathode material, including: Mixing a lithium-rich manganese-based precursor with a lithium source and a crystal structure stabilizer to obtain a mixed material A; Performing a first sintering on the mixed material A and pulverizing to obtain a material B; Mixing the material B with an MSe@Te heterojunction to obtain a material C; Performing a second sintering on the material C to obtain the lithium-rich manganese-based cathode material.

[0009] In some embodiments, the preparation method of the MSe@Te heterojunction includes: Mixing M x Se y and M x Te y , performing sand milling and spray drying, and then performing calcination and ball milling to obtain the MSe@Te heterojunction; And satisfying at least one of the following conditions: A. The molar ratio of the M x Se y and the M x Te y is 1:(0.1 - 10); B. The calcination temperature is 400 - 700 °C, and the calcination time is 5 - 8 h; C. The ball milling speed is 300 - 600 r / min, and the ball milling time is 15 - 60 min.

[0010] In some embodiments, the crystal structure stabilizer is a metal fluoride. The metal fluoride includes a first metal fluoride and a second metal fluoride. The first metal fluoride is MgF 2 , and the valence state of the metal cation of the second metal fluoride is ≥ +2, and satisfies at least one of the following conditions: A. The metal cation includes at least one of La, Ta, Sr, Y, Ce, and Sb; B. Based on the mass of the lithium-rich manganese-based precursor, the MgF 2 The addition amount is 1000~2500ppm; C. Based on the mass of the lithium-rich manganese-based precursor, the amount of the second metal fluoride added is 500-2000 ppm; D. The size of the MSe@Te heterojunction is less than 50 nm; E. Based on the mass of the material B, the added amount of the MSe@Te heterojunction is 1500-4000 ppm.

[0011] In some embodiments, at least one of the following conditions is met: A. The lithium-rich manganese-based precursor includes Ni x Mn y (OH) 2 、Ni x Mn y CO 3 、Ni x Mn y One or more of O, where 0.25≤x≤0.80, 0.20≤y≤0.75; B. The lithium source includes LiOH·H 2 O. Li 2 CO 3 , CH 3 COOLi, Li 2 C 2 O 4 、LiNO 3 One or more of the following; C. D50 of the lithium source is 1 μm to 20 μm; D. The molar ratio of the lithium-rich manganese-based precursor to the lithium source is 1: (1.2-1.6); E. The first sintering includes: firstly heating from room temperature to 500-750°C at a heating rate of 1-10°C / min, and keeping the temperature for 4-9h, then heating to 850-1000°C at a heating rate of 10-15°C / min, and keeping the temperature for 11-18h; F. The second sintering temperature is 370-750°C, the time is 6-18h, and the heating rate is 5-10°C / min; G. Gas is introduced into the first sintering and the second sintering, and the gas is air, pure oxygen or a mixed gas with an oxygen concentration of ≥20%, and the gas flow rate is 50-100 L / h.

[0012] The present application also provides a positive electrode sheet, comprising the above-mentioned lithium-rich manganese-based positive electrode material.

[0013] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode sheet.

[0014] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0015] Compared with the prior art, the beneficial effects of this application include: The lithium-rich manganese-based positive electrode material provided in the present application is doped with anionic fluorine, first cation Mg and second cation with a higher valence, and the coating layer is a MSe@Te heterojunction coating layer. The lithium-rich manganese-based material is doped with cations with a higher valence to enhance the lithium ion migration kinetics and improve the rate performance of the material by regulating the charge distribution in the crystal structure; Mg 2+ After element doping, a strong MO bonding reaction is formed inside the material, which improves the Li 2 MnO 3 The structural stability of the crystal under high voltage conditions inhibits the Li 2 MnO 3 The irreversible loss of lattice oxygen caused by high voltage charging reduces the loss of first cycle capacity. Fluorine doping replaces part of the oxygen in the bulk phase to stabilize Li 2 MnO 3 The bulk structure of the crystal inhibits the generation of Li 2 MnO 3 The irreversible phase change caused by oxygen release improves the electrochemical properties of the material; the bulk doping of fluorine is beneficial to inhibit the corrosion of the electrolyte on the material, reduce the formation of the side reaction product LiF on the surface of the material, improve the stability of the reaction interface, and improve the cycle performance.

[0016] The MSe@Te coating prevents the electrolyte from directly contacting the material surface, reduces the occurrence of interface side reactions and the uneven accumulation of byproducts with poor conductivity on the material surface at high charge cut-off voltage, limits the growth of impedance during the cycle, and solves the problem of poor rate performance of lithium-rich manganese-based materials; the MSe@Te coating alleviates the Li 2 MnO 3 The loss of lattice oxygen on the crystal surface and the migration of oxygen in the bulk phase to the surface avoid the destruction of the material surface structure and the occurrence of irreversible capacity loss and voltage decay caused by continuous phase change, improve the surface interface stability, and solve the problem of poor cycle stability of lithium-rich manganese-based materials; Se and Te form a heterogeneous structure during the sintering process, and the coating of MSe@Te greatly improves the migration rate of lithium ions and enhances the electrochemical performance of lithium-rich manganese-based materials.

[0017] The preparation method of the lithium-rich manganese-based positive electrode material provided in the present application adopts a crystal structure stabilizer, a lithium-rich manganese-based precursor, and a lithium source to mix and sinter, dope and modify the lithium-rich manganese-based positive electrode material, and use MSe@Te heterojunction for coating to synergistically improve the lithium-rich manganese-based positive electrode material to improve Li 2 MnO 3 structural stability and improve electrochemical performance.

[0018] The positive electrode sheet, lithium-ion battery and electrical equipment provided in the present application adopt the above-mentioned lithium-rich manganese-based positive electrode material, which can simultaneously have a higher discharge capacity, a higher discharge first efficiency and an excellent rate discharge capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0020] Figure 1 A schematic diagram of a process for preparing a lithium-rich manganese-based positive electrode material of the present application; Figure 2 This is a SEM image of the lithium-rich manganese-based positive electrode material of Example 1; Figure 3 This is a SEM image of the lithium-rich manganese-based positive electrode material of Comparative Example 2; Figure 4 This is a SEM image of the lithium-rich manganese-based positive electrode material of Comparative Example 3; Figure 5 This is a SEM image of the lithium-rich manganese-based positive electrode material of Comparative Example 4; Figure 6 This is the SEM image of the lithium-rich manganese-based positive electrode material of Comparative Example 5. DETAILED DESCRIPTION

[0021] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0022] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0023] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0024] In these examples, parts and percentages are by mass unless otherwise indicated.

[0025] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0026] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0028] The present application provides a lithium-rich manganese-based positive electrode material, comprising a lithium-rich manganese-based core and a coating layer coating the core, wherein the core is doped with anion fluorine, a first cation Mg and a second cation, the valence state of the second cation is ≥+2, and the coating layer is a MSe@Te heterojunction coating layer, wherein M is selected from any one of Mo, W, Sn, and Bi.

[0029] The lithium-rich manganese-based positive electrode material provided in the present application is modified by doping with cations with a higher valence state, and the charge distribution in the crystal structure is regulated to enhance the lithium ion migration kinetics and improve the rate performance of the material; Mg 2+ After element doping, a strong MO bonding reaction is formed inside the material, which improves the Li 2 MnO 3 The structural stability of the crystal under high voltage conditions inhibits the Li 2 MnO 3 The irreversible loss of lattice oxygen caused by high voltage charging reduces the loss of first cycle capacity. Fluorine doping replaces part of the oxygen in the bulk phase to stabilize Li 2 MnO 3 The bulk structure of the crystal inhibits the generation of Li 2 MnO 3 The irreversible phase change caused by oxygen release improves the electrochemical properties of the material; the bulk doping of fluorine is beneficial to inhibit the corrosion of the electrolyte on the material, reduce the formation of the side reaction product LiF on the surface of the material, improve the stability of the reaction interface, and improve the cycle performance.

[0030] The MSe@Te coating prevents the electrolyte from directly contacting the material surface, reduces the occurrence of interface side reactions and the uneven accumulation of byproducts with poor conductivity on the material surface at high charge cut-off voltage, limits the growth of impedance during the cycle, and solves the problem of poor rate performance of lithium-rich manganese-based materials; the MSe@Te coating alleviates the Li 2 MnO 3 The loss of lattice oxygen on the crystal surface and the migration of oxygen in the bulk phase to the surface avoid the destruction of the material surface structure and the occurrence of irreversible capacity loss and voltage decay caused by continuous phase change, improve the surface interface stability, and solve the problem of poor cycle stability of lithium-rich manganese-based materials; Se and Te form a heterogeneous structure during the sintering process, and the coating of MSe@Te greatly improves the migration rate of lithium ions and enhances the electrochemical performance of lithium-rich manganese-based materials.

[0031] In some embodiments, the second cation is selected from at least one of Y, Ta, La, Ce, Sr, and Sb.

[0032] In some embodiments, the lithium-rich manganese-based cathode material is spherical-like particles; the D50 of the lithium-rich manganese-based cathode material is 8-12 μm, for example, it can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any value between 8-12 μm.

[0033] In some embodiments, calculated by the mass equivalent of element M, the addition amount of the heterojunction coating layer is 1500 ppm - 4000 ppm, for example, it can be 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, 3100 ppm, 3200 ppm, 3300 ppm, 3400 ppm, 3500 ppm, 3600 ppm, 3700 ppm, 3800 ppm, 3900 ppm, 4000 ppm or any value between 1500 ppm - 4000 ppm, and the calculation basis is the weight of the lithium-rich manganese-based cathode material excluding the coating layer.

[0034] If the addition amount of the heterojunction coating layer is lower than the above range, it is difficult to obtain a uniform and complete coating layer. If the addition amount is higher than the above range, too much heterojunction completely wraps on the surface of the lithium-rich manganese-based cathode material, and the grain boundaries of the primary particles become blurred until they are completely covered and invisible. Li + migration impedance increases. Under the condition of rate discharge, Li + cannot be quickly output / imported, and the electrical performance is partially affected.

[0035] In some embodiments, the chemical general formula of the lithium-rich manganese-based core is: t Li 2 MnO 3 ·(1 - t)LiNO 2 , where 0 < t < 1, and N is selected from at least one of Ni, Co, and Mn.

[0036] In some embodiments, the lithium-rich manganese-based core includes a plurality of primary particles, and the aspect ratio of the primary particles is between (1:1) - (5:1), for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1 or any value between (1:1) - (5:1).

[0037] This application also provides a preparation method of the above lithium-rich manganese-based cathode material. Please refer to Figure 1 , including: S100: Mix the lithium-rich manganese-based precursor with a lithium source and a crystal structure stabilizer to obtain a mixed material A; S200: sintering the mixed material A for the first time and crushing it to obtain material B; S300: mixing material B with the MSe@Te heterojunction to obtain material C; S400: sintering material C for a second time to obtain a lithium-rich manganese-based positive electrode material.

[0038] The preparation method of the lithium-rich manganese-based positive electrode material provided in the present application adopts a crystal structure stabilizer, a lithium-rich manganese-based precursor, and a lithium source to mix and sinter, dope and modify the lithium-rich manganese-based positive electrode material, and use MSe@Te heterojunction for coating to synergistically improve the lithium-rich manganese-based positive electrode material to improve Li 2 MnO 3 structural stability and improve electrochemical performance.

[0039] Although there are other types of heterojunctions in the prior art, such as MoC@Mo 2 C type carbide heterojunction, but because the lithium-rich manganese sintering is air or oxygen, the carbide heterojunction will generate carbon dioxide volatilization in an oxygen-containing atmosphere, and the heterojunction will not work. Therefore, the lithium-rich manganese-based positive electrode material of the present application can only be coated with the MSe@Te heterojunction of the present application to achieve the required effect of the present application.

[0040] In some embodiments, the method for preparing the MSe@Te heterojunction comprises: M x Se y and M x Te y The mixture is sand-milled and spray-dried, then calcined and ball-milled to obtain the MSe@Te heterojunction.

[0041] Among them, the M x Se y and the M x Te y The molar ratio of M can be any molar ratio. x Se y and the M x Te y The molar ratio is 1:(0.1-10), for example, it can be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any ratio between 1:(0.1-10).

[0042] Wherein, the calcination temperature is 400-700°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C or any value between 400-700°C, and the calcination time is 5-8h, for example, it can be 5h, 6h, 7h, 8h or any value between 5-8h.

[0043] Wherein, the ball milling speed is 300~600r / min, for example, it can be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min or any value between 300~600r / min, and the ball milling time is 15~60min, for example, it can be 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value between 15~60min.

[0044] In some embodiments, the crystal structure stabilizer is a metal fluoride, and the metal fluoride includes a first metal fluoride and a second metal fluoride, and the first metal fluoride is MgF 2 , the valence state of the metal cation of the second metal fluoride is ≥ +2, wherein the metal cation includes at least one of La, Ta, Sr, Y, Ce, and Sb.

[0045] In some embodiments, based on the mass of the lithium-rich manganese-based precursor, the MgF 2 The amount of MgF added is 1000-2500ppm, for example, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm or any value between 1000 and 2500ppm. 2 The amount of addition is calculated based on the mass equivalent of the Mg element.

[0046] In some embodiments, based on the mass of the lithium-rich manganese-based precursor, the amount of the second metal fluoride added is 500~2000ppm, for example, it can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm or any value between 500~2000ppm, and the amount of the second metal fluoride added is calculated based on the mass equivalent of the corresponding metal cation element.

[0047] In some embodiments, the size of the MSe@Te heterojunction is less than 50 nm; based on the mass of the material B, the addition amount of the MSe@Te heterojunction is 1500-4000 ppm, for example, it can be 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, 3100 ppm, 3200 ppm, 3300 ppm, 3400 ppm, 3500 ppm, 3600 ppm, 3700 ppm, 3800 ppm, 3900 ppm, 4000 ppm or any value between 1500 ppm and 4000 ppm.

[0048] In some embodiments, the lithium-rich manganese-based precursor includes Ni x Mn y (OH) 2 、Ni x Mn y CO 3 、Ni x Mn y One or more of O, wherein 0.25≤x≤0.80, 0.20≤y≤0.75.

[0049] In some embodiments, the lithium source includes LiOH·H 2 O. Li 2 CO 3 , CH 3 COOLi, Li 2 C 2 O 4 、LiNO 3The D50 of the lithium source is 1 μm to 20 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm or any value between 1 μm and 20 μm.

[0050] In some embodiments, the molar ratio of the lithium-rich manganese-based precursor to the lithium source is 1:(1.2-1.6), for example, it can be 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6 or any value between 1:(1.2-1.6).

[0051] In some embodiments, the first sintering includes: first heating from room temperature to 500-750°C at a heating rate of 1-10°C / min, and keeping warm for 4-9 hours, then heating to 850-1000°C at a heating rate of 10-15°C / min, and keeping warm for 11-18 hours.

[0052] In some embodiments, the second sintering temperature is 370-750° C., the time is 6-18 hours, and the heating rate is 5-10° C. / min.

[0053] In some embodiments, gas is introduced during the first sintering and the second sintering, and the gas is air, pure oxygen, or a mixed gas with an oxygen concentration of ≥ 20%, and the gas flow rate is 50-100 L / h.

[0054] The present application also provides a positive electrode sheet, comprising the above-mentioned lithium-rich manganese-based positive electrode material.

[0055] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode sheet.

[0056] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0057] The positive electrode sheet, lithium-ion battery and electrical equipment provided in the present application adopt the above-mentioned lithium-rich manganese-based positive electrode material, which can simultaneously have a higher discharge capacity, a higher discharge first efficiency and an excellent rate discharge capacity.

[0058] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0059] Example 1 This embodiment provides a lithium-rich manganese-based positive electrode material, and the preparation method thereof comprises the following steps: (1) Weigh 5 kg of lithium-rich manganese-based precursor Ni at a ratio of 1:1.38 (molar ratio) 0.35 Mn 0.65 (OH) 2 and 2.82kg Li 2 CO 3 , and add 25.8g (2000ppm) MgF 2 and 8.2g (1000ppm) YF 3 , and mix at high speed in a high-speed mixer to obtain a mixed material A. Mixed material A is placed in a bowl and placed in a tube furnace to introduce air (gas flow rate 80L / h), and first heated to 620°C at a rate of 7°C / min and kept at a constant temperature for 6h. After the constant temperature is completed, the temperature is then increased to 962°C at a rate of 12°C / min and kept at a constant temperature for 13h. After the constant temperature is completed, it is naturally cooled to room temperature and pulverized to obtain material B; (2) Weigh a certain amount of MoSe at a molar ratio of 1:1 2 and MoTe 2 After sand milling and spray drying, the mixture was transferred into a muffle furnace and calcined at 610°C for 7 hours. After calcination, the mixture was naturally cooled to room temperature. After cooling, the mixture was added into a ball mill and the ball milling speed was set to 450 r / min. The mixture was milled for 35 minutes to obtain a MoSe@Te heterojunction. (3) 5 kg of material B and 39.4 g (2500 ppm) of MoSe@Te were added to a high-speed mixer for high-speed mixing and dispersion to obtain material C. After the mixing was completed, material C was placed in a box furnace and air was introduced (gas flow rate 80 L / h). The temperature was raised to 635°C at a rate of 8°C / min and kept constant at this temperature for 12.5 hours. After the constant temperature was completed, it was naturally cooled to room temperature. After the cooling was completed, the modified lithium-rich manganese-based positive electrode material of Example 1 with a D50 of about 9.5 μm was obtained.

[0060] The SEM image of the lithium-rich manganese-based positive electrode material of Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the lithium-rich manganese-based positive electrode material after coating modification is a spherical particle, the surface of which is evenly coated by the molten nano-heterojunction. The molten nano-heterojunction covers the particle surface and grain boundaries. The electron microscope image proves that when the amount of nano-heterojunction added is the same, only the element type is changed, and the surface morphology of the lithium-rich manganese-based positive electrode material has no significant effect. The addition or not of the structural stabilizer has no obvious effect on the surface morphology of the lithium-rich manganese-based positive electrode material.

[0061] Example 2 The difference between Example 2 and Example 1 is that the raw material in step (1) is 5 kg of lithium-rich manganese-based precursor Ni 0.35 Mn 0.65 (OH) 2and 2.82kg Li 2 CO 3 , and add 25.8g (2000ppm) MgF 2 and 7.6 g (1000 ppm) TaF 5 , the other steps and conditions are the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Example 2 with a modified D50 of about 9.5 μm is obtained.

[0062] Example 3 The difference between Example 3 and Example 1 is that the raw material in step (1) is 5 kg of lithium-rich manganese-based precursor Ni 0.35 Mn 0.65 (OH) 2 and 2.82kg Li 2 CO 3 , and add 25.8g (2000ppm) MgF 2 and 7.7g (1000ppm) CeF 4 , the other steps and conditions are the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Example 3 with a modified D50 of about 9.5 μm is obtained.

[0063] Example 4 The difference between Example 4 and Example 1 is that the raw material in step (1) is 5 kg of lithium-rich manganese-based precursor Ni 0.35 Mn 0.65 (OH) 2 and 2.82kg Li 2 CO 3 , and add 25.8g (2000ppm) MgF 2 and 7.0 g (1000 ppm) LaF 3 , the other steps and conditions are the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Example 4 with a modified D50 of about 9.5 μm is obtained.

[0064] Example 5 The difference between Example 5 and Example 1 is that the raw material in step (2) is WSe 2 and WTe 2 In step (3), 5 kg of material B and 26.5 g (2500 ppm) of WSe@Te were weighed, and the other steps and conditions were the same as those in Example 1. Finally, the lithium-rich manganese-based positive electrode material of Example 5 with a modified D50 of about 9.5 μm was obtained.

[0065] Example 6 The difference between Example 6 and Example 1 is that the raw material in step (2) is SnSe 2 and SnTe 2In step (3), 5 kg of material B and 34.2 g (2500 ppm) of SnSe@Te were weighed, and the other steps and conditions were the same as those in Example 1. Finally, the lithium-rich manganese-based positive electrode material of Example 6 with a modified D50 of about 9.5 μm was obtained.

[0066] Example 7 The difference between Example 7 and Example 1 is that: in step (1), YF 3 The addition amount was reduced to 4.1 g (500 ppm), and the other steps and conditions were the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Example 7 with a modified D50 of about 9.5 μm was obtained.

[0067] Example 8 The difference between Example 8 and Example 1 is that in step (1), YF 3 The addition amount was increased to 16.4 g (2000 ppm), and the other steps and conditions were the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Example 8 with a modified D50 of about 9.5 μm was obtained.

[0068] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that YF is not added in step (1). 3 , the other steps and conditions are the same as those in Example 1, and finally the lithium-rich manganese-based positive electrode material of Comparative Example 1 with a modified D50 of about 9.5 μm is obtained.

[0069] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step (2) and step (3) are not performed, and the other steps and conditions are the same as those of Example 1. Finally, the lithium-rich manganese-based positive electrode material of Comparative Example 2 with a modified D50 of about 9.5 μm is obtained.

[0070] The SEM image of the lithium-rich manganese-based positive electrode material of Comparative Example 2 is as follows: Figure 3 As shown, Figure 3 It is shown that when no nano-heterojunction is used for coating modification, the surface grain boundaries of the lithium-rich manganese-based positive electrode material of Comparative Example 2 are clearly visible, and the aspect ratio of the primary grains is between 1:1-5:1.

[0071] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the amount of MoSe@Te added in step (3) is reduced to 15.8 g (1000 ppm), and the other steps and conditions are the same as those in Example 1. Finally, the lithium-rich manganese-based positive electrode material of Comparative Example 3 with a D50 of about 9.5 μm after modification is obtained, and its SEM image is as follows: Figure 4 As shown, according to Figure 4 It can be seen that the addition amount of MoSe@Te is too low and cannot form a uniform coating layer on the surface of the lithium-rich manganese-based positive electrode material.

[0072] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the amount of MoSe@Te added in step (3) is increased to 78.8 g (5000 ppm), and the other steps and conditions are the same as those in Example 1. Finally, the lithium-rich manganese-based positive electrode material of Comparative Example 4 with a D50 of about 9.5 μm after modification is obtained, and its SEM image is as follows: Figure 5 As shown, according to Figure 4 and Figure 5 It can be seen from the comparison that when the coating amount of the nano-heterojunction is continuously increased, the grain boundaries of the primary particles of the positive electrode material gradually become blurred until they are completely covered and invisible.

[0073] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that step (2) is not performed, and in step (3), 5 kg of material B and 45.8 g (2500 ppm) of MoTe are weighed. 2 Finally, the lithium-rich manganese-based positive electrode material of comparative example 5 with a D50 of about 9.5 μm after modification is obtained, and its SEM image is as follows Figure 6 As shown, it can be seen that the coating layer is only MoTe 2 , lithium-rich manganese-based cathode materials can form similar surface morphologies.

[0074] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that step (2) is not performed, and in step (3), 5 kg of material B and 33.1 g (2500 ppm) of MoSe are weighed. 2 Finally, the lithium-rich manganese-based positive electrode material of Comparative Example 6 with a modified D50 of about 9.5 μm was obtained.

[0075] Electrochemical performance test The electrochemical performance test steps of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-6 are as follows: (1) Preparation of PVDF glue: weigh the corresponding amount of PVDF and NMP solvent in a mass ratio of 0.3% into a beaker and stir at 300r for 30min; (2) Weigh a certain amount of lithium-rich manganese-based positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-6 in a ratio of 94:4:2 (mass ratio), add conductive carbon black and a binder to the PVDF glue prepared in step (1), and continue stirring for 20 minutes until no bubbles appear in the beaker to obtain a positive electrode slurry; (3) The positive electrode slurry prepared in step (2) is evenly coated on the aluminum foil with a scraper, and the coated electrode is placed in a vacuum drying oven at 110° C. for 12 h. After drying, a positive electrode sheet with a diameter of 14 mm is punched out with a slicer, and the sheet is weighed and set aside; (4) Assemble a CR2025 button cell in the glove box in the order of positive electrode shell-positive electrode sheet-diaphragm-electrolyte-lithium sheet-gasket-spring-negative electrode shell, and then take it out and package it in a packaging machine to obtain a button cell; (5) At a temperature of 25°C, use the Xinwei battery tester to complete the charge, discharge and rate performance tests at a voltage of 2.5V-4.5V.

[0076] The test results of various embodiments and comparative examples are shown in Table 1.

[0077] Table 1 Electrochemical performance test data

[0078] As can be seen from Table 1, Examples 1-6 can simultaneously have a high discharge capacity, a high discharge first efficiency and an excellent rate discharge capacity, and their comprehensive performance is significantly better than that of Comparative Examples 1-6. The capacity of the battery assembled from the positive electrode materials of Examples 1-6 is above 200mAh / g, and the discharge first efficiency is maintained at above 80%. By changing the type of metal elements of the crystal structure stabilizer and the nanoheterojunction, the capacity and first efficiency fluctuate slightly, but are generally at the same level.

[0079] Comparative Example 1, Example 7, and Example 8 reduce / improve the removal of MgF on the basis of Example 1. 2 The amount of crystal structure stabilizer added is different. Comparative Example 1 does not add any structure stabilizer, the amount added in Example 7 is lower than that in Example 1, and the amount added in Example 8 is higher than that in Example 1. It can be seen from Table 1 that under the conditions of Comparative Example 1 and Example 7, the capacity and initial efficiency of the positive electrode material are significantly reduced, while under the conditions of Example 8, the capacity reduction is not obvious (~200mAh / g). The above proves that the crystal structure stabilizer has a significant effect on the structural stability of the lithium-rich manganese-based positive electrode material. When the operating voltage is high and the lithium-rich manganese-based positive electrode material is in a deep delithiation state, the Li 2 MnO 3 The unstable oxygen atoms in the phase are removed from Li 2 MnO 3 In the lattice, O 2 The irreversible release of oxygen causes the structure of the lithium-rich manganese-based positive electrode material to collapse and deform, resulting in a significant decrease in capacity and initial efficiency. When the added amount is high, the excess crystal structure stabilizer will occupy the active sites of Li ions in the electrochemical process, causing active Li loss, resulting in a slight decrease in capacity and initial efficiency.

[0080] Comparative Examples 2 to 4 adjust the coating amount of the nano heterojunction based on the steps of Example 1. Comparative Example 2 does not add the nano heterojunction, the addition amount of the nano heterojunction in Comparative Example 3 is relatively low, and the addition amount of the nano heterojunction in Comparative Example 4 is the highest. It can be seen from Table 1 that when no nano heterojunction is added, too little nano heterojunction is added, or too much nano heterojunction is added, the discharge capacity, first discharge efficiency, and rate discharge capacity of the lithium-rich manganese-based positive electrode material are lost to varying degrees. When no nano heterojunction coating is performed, the lithium-rich manganese-based positive electrode material has poor rate performance and conductivity due to the influence of its own internal structural phase state, so the discharge capacity and cycle retention rate are low and the loss is large.

[0081] When the amount of nano-heterojunction added is low, the heterojunction coating formed is uneven and incomplete, and the Li + During transmission, it can be affected by the quantum effect and interface effect of the heterojunction, so the electrical performance is improved, but the overall performance is poor; when the amount of added heterojunction is high, too much heterojunction is completely wrapped on the surface of the lithium-rich manganese-based positive electrode material, Li + The migration impedance increases, and under the discharge rate condition, Li + The electrical properties are partially affected because the output / import cannot be fast. Comparative Examples 5 and 6 are modified by using a single metal telluride and selenide, and the addition amount is the same as that of Example 1. The single metal telluride and selenide have limited effects and cannot play the corresponding role of heterojunction, so the electrical properties are worse than those of Example 1.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0083] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A lithium-rich manganese-based positive electrode material, characterized in that: It includes a lithium-rich manganese-based core and a coating layer that coats the core. The core is doped with anionic fluorine, a first cation Mg, and a second cation, and the valence state of the second cation is ≥ +2. The coating layer is an MSe@Te heterojunction coating layer, where M is selected from any one of Mo, W, Sn, and Bi.

2. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The second cation is selected from at least one of Y, Ta, La, Ce, Sr, and Sb.

3. The lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: Meet at least one of the following conditions: A. The lithium-rich manganese-based cathode material is spherical-like particles. B. Calculated by the mass equivalent of element M, the addition amount of the heterojunction coating layer is 1500 ppm to 4000 ppm. C. The chemical general formula of the lithium-rich manganese-based core is: t Li2MnO3·(1 - t)LiNO2, where 0 < t < 1, and N is selected from at least one of Ni, Co, and Mn. D. The lithium-rich manganese-based core includes a plurality of primary particles, and the aspect ratio of the primary particles is in the range of (1:1) to (5:1). E. The D50 of the lithium-rich manganese-based cathode material is 8 to 12 μm.

4. A method for preparing a lithium-rich manganese-based positive electrode material according to any one of claims 1 to 3, characterized in that: It includes: Mix the lithium-rich manganese-based precursor with a lithium source and a crystal structure stabilizer to obtain a mixed material A. Perform the first sintering on the mixed material A and crush it to obtain a material B. Mix the material B with the MSe@Te heterojunction to obtain a material C. Perform the second sintering on the material C to obtain the lithium-rich manganese-based cathode material.

5. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: The preparation method of the MSe@Te heterojunction includes: M x Se y and M x Te y The mixture is sand-milled and spray-dried, and then calcined and ball-milled to obtain the MSe@Te heterojunction; And meet at least one of the following conditions: A. The M x Se y and the M x Te y The molar ratio is 1: (0.1~10); B. The calcination temperature is 400 to 700 °C, and the calcination time is 5 to 8 h. C. The ball milling speed is 300 to 600 r / min, and the ball milling time is 15 to 60 min.

6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: The crystal structure stabilizer is a metal fluoride, and the metal fluoride includes a first metal fluoride and a second metal fluoride. The first metal fluoride is MgF2, and the metal cation of the second metal fluoride has a valence state ≥ +2, and meet at least one of the following conditions: A. The metal cation includes at least one of La, Ta, Sr, Y, Ce, and Sb. B. Based on the mass of the lithium-rich manganese-based precursor, the addition amount of MgF2 is 1000 to 2500 ppm. C. Based on the mass of the lithium-rich manganese-based precursor, the addition amount of the second metal fluoride is 500 to 2000 ppm. D. The size of the MSe@Te heterojunction is less than 50 nm. E. Based on the mass of the material B, the addition amount of the MSe@Te heterojunction is 1500 - 4000 ppm.

7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: Meet at least one of the following conditions: A. The lithium-rich manganese-based precursor includes Ni x Mn y (OH)2、Ni x Mn y CO3、Ni x Mn y One or more of O, where 0.25≤x≤0.80, 0.20≤y≤0.75; B. The lithium source includes one or more of LiOH·H2O, Li2CO3, CH3COOLi, Li2C2O4, and LiNO3. C. The D50 of the lithium source is 1 μm to 20 μm. D. The molar ratio of the lithium-rich manganese-based precursor to the lithium source is 1:(1.2 - 1.6). E. The first sintering includes: firstly heating from room temperature to 500-750°C at a heating rate of 1-10°C / min, and keeping the temperature for 4-9h, then heating to 850-1000°C at a heating rate of 10-15°C / min, and keeping the temperature for 11-18h; F. The second sintering temperature is 370-750°C, the time is 6-18h, and the heating rate is 5-10°C / min; G. Gas is introduced into the first sintering and the second sintering, and the gas is air, pure oxygen or a mixed gas with an oxygen concentration of ≥20%, and the gas flow rate is 50-100 L / h.

8. A positive electrode sheet, characterized in that: The invention comprises the lithium-rich manganese-based positive electrode material as described in any one of claims 1 to 3.

9. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.

10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Cr3&lt;+&gt;, Mg&lt;2+&gt;, Fe&lt;3+&gt; and F&lt;-&gt; co-doped composite lithium-rich anode material and preparation method thereof

    CN103078101A

  • Modified lithium nickel cobalt manganese cathode material and production method thereof

    CN107591519A

  • Hydrothermal method for preparing SnSe2 / CNTs composite lithium ion battery electrode material

    CN110190268A

  • Lithium-rich manganese-based precursor and preparation method thereof, lithium-rich manganese-based positive electrode material and preparation method thereof, and lithium ion battery

    CN112234176A

  • Molybdenum diselenide coated cobalt-free high-nickel positive electrode material as well as preparation method and application thereof

    CN115528230A